Phase and dark‐field imaging with mesh‐based structured illumination and polycapillary optics. Issue 11 (11th October 2021) - Pyakurel, Uttam; Sun, Weiyuan; Cheung, Pikting; D'Moore, Desirée; Zhang, Xiaoyun; MacDonald, Carolyn A.; Petruccelli, Jonathan C.
Abstract: Purpose: X‐ray phase and dark‐field (DF) imaging have been shown to improve the diagnostic capabilities of X‐ray systems. However, these methods have found limited clinical use due to the need for multiple precision gratings with limited field of view or requirements on X‐ray coherence that may not be easily translated to clinical practice. This work aims to develop a practicable X‐ray phase and DF imaging system that could be translated and practiced in the clinic. Methods: This work employs a conventional source to create structured illumination with a simple wire mesh. A mesh‐shifting algorithm is used to allow wider Fourier windowing to enhance resolution. Deconvolution of the source spot width and camera resolution improves accuracy. Polycapillary optics are employed to enhance coherence. The effects of incorporating optics with two different focal lengths are compared. Information apparent in enhanced absorption images, phase images, and DF images of fat embedded phantoms were compared and subjected to a limited receiver operator characteristic (ROC) study. The DF images of the moist and dry porous object (sponges) were compared. Results: The mesh‐based phase and DF imaging system constructs images with three different information types: scatter‐free absorption images, differential phase images, and scatter magnitude/DF images, simultaneously from the same original image. The polycapillary optic enhances the coherence of the beam. The deblurring technique corrects the phase signal error due to geometrical blur and the limitation of the camera modulation transfer function (MTF) and removes image artifacts to improve the resolution in a single shot. The mesh‐shifting method allows the use of a wider Fourier processing window, which gives even higher resolution, at the expense of an increased dose. The limited ROC study confirms the efficacy of the system over the conventional system. DF images of moist and dry porous object show the significance of the system in the imaging of lung infections. Conclusion: The mesh‐based X‐ray phase and DF imaging system is an inexpensive and easy setup in terms of alignment and data acquisition and can produce phase and DF images in a single shot with wide field of view. The system shows significant potential for use in diagnostic imaging in a clinical setting.